PROSES BERPIKIR SIBERNETIK DALAM MATERI MEYAKINI KITAB-KITAB ALLAH DAN MENCINTAI AL-QUR’AN KELAS VIII SMP - Reksahati Wulandari; Nurul Azizatul Isnaini; Nadya Ilma Rosyda; Tarsono Tarsono; Hasbiyallah Hasbiyallah (Jurnal Muara Pendidikan, 2023)
The cybernetic theory developed by Landa is closely related to a process, but apart from the learning process, there is another more focused process, namely the thinking process which can be reflected in the activities in the learning material. This research is intended to examine the cybernetic thinking process in activities that must be carried out by students in the material of believing in the books of Allah and loving the Koran in the Islamic education and character books for class VIII middle school. This research uses qualitative methods with literature study which is then explained and described in the results and discussion. The results of this research suggest that the activities in the Islamic education and character books for class VIII SMP in the material of believing in the books of Allah and loving the Koran contain cybernetic thinking processes.